2014
DOI: 10.3109/14992027.2014.969409
|View full text |Cite
|
Sign up to set email alerts
|

Computer-based auditory phoneme discrimination training improves speech recognition in noise in experienced adult cochlear implant listeners

Abstract: Phoneme-discrimination training improves experienced CI listeners' speech perception in noise. Additional research is needed to optimize auditory training for individual benefit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
0
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 23 publications
4
49
0
4
Order By: Relevance
“…For this reason, we investigated the correlation between the WRS 65 (CI) after 6 months and the preoperative WRS max in order further to minimize the variability. Future studies may investigate the influence of rehabilitation, motivation, communicative environment, and additional training measures [ 26 , 29 ]. These variables are difficult to control for large patient groups and were therefore not taken into account in this study.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, we investigated the correlation between the WRS 65 (CI) after 6 months and the preoperative WRS max in order further to minimize the variability. Future studies may investigate the influence of rehabilitation, motivation, communicative environment, and additional training measures [ 26 , 29 ]. These variables are difficult to control for large patient groups and were therefore not taken into account in this study.…”
Section: Discussionmentioning
confidence: 99%
“…All studies showed retention of learning to trained and untrained measures to various degrees with only some reporting the statistical effects. Recently, other studies have demonstrated significant retention of learning, 43,46,47 with the possibility of top-up sessions remaining as a means to maintain learning-related benefits. 48 What Is the Adherence of Individuals with Computer-based Training?…”
Section: Does Any Improvement In Trained and Untrained Measures Remaimentioning
confidence: 99%
“…Bezüglich der Gegenseite werden heute Schwerhörige mit allen Graden asymmetrischen Hörverlusts bis hin zur Normalhörigkeit erfolgreich mit CI versorgt [1,16,20]. Gründe hierfür waren die kontinuierliche Verbesserung der CI-Versorgung im Bereich der Chirurgie [19,20], der Technologie [2,7,8,17,28] und der Rehabilitation [26,29]. Auch wurden zunehmend Patienten mit substanziellem präoperativem Gehör auf der zu versorgenden Seite für eine Cochleaimplantation in Betracht gezogen [27].…”
Section: Hintergrundunclassified
“…Aus diesem Grund wurde das EV65(CI) nach 6 Monaten mit dem mEV korreliert, um die Variabilität weiter zu minimieren. Zukünftige Studien könnten den Einfluss der Rehabilitation, Motivation, Kommunikationsumgebung und zusätzlicher Rehabilitationsmaßnahmen analysieren [26,29]. Die genannten Variablen sind in der klinischen Routine für große Patientengruppen schwer zu kontrollieren und wurden in dieser Studie nicht berücksichtigt.…”
Section: Sprachverstehen Mit CI Im Langfristigen Verlaufunclassified